Systemic perspectives on Intimate Partner Violence treatment - Stith, Sandra M.; McCollum, Eric E.; Amanor-Boadu, Yvonne; Smith, Douglas (My University, 2013)
This paper reviews changes in the research literature on Intimate Partner Violence (IPV) since our earlier review (Stith, Rosen, & McCollum, 2003). A rationale for systemic treatment of IPV has emerged from research that has continued to document the limited effectiveness of single gender treatment approaches for offenders and that has identified sub-types of abusive relationships, including Situational Couple Violence, that often includes the reciprocal use of violence. Consistent findings from the available outcome research have demonstrated that for carefully screened couples who choose to stay together, systemic interventions decrease incidences of IPV and decrease the risk factors for IPV with no increase in risk. Implications for research and treatment are offered.
Keywords: Intimate partner violence; Abusive relationships; Situational couple violence